2016
DOI: 10.15405/epsbs.2016.08.40
|View full text |Cite
|
Sign up to set email alerts
|

A Modernize Tax Administration Model for Revenue Generation

Abstract: Capacity of a government to finance it expenditure depend on the ability of tax system to generate adequate revenue, and the ability of tax system to generate significant revenue depend on the tax administration efficiency and effectiveness, however in most of the developing economies, tax administration is characterized by inefficiency and ineffectiveness. The objective of this paper to develop a model which will guide developing countries to reform their tax administration toward tax revenue promising. To ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…The result showed that there is a significant relationship between accounting information and production decisions. This result follows the study of Pantamee et al (2008). The findings of their research work led them to conclude that there is a significant relationship between management accounting information and managerial decision making in the manufacturing industry.…”
Section: Hypothesis Threesupporting
confidence: 75%
See 1 more Smart Citation
“…The result showed that there is a significant relationship between accounting information and production decisions. This result follows the study of Pantamee et al (2008). The findings of their research work led them to conclude that there is a significant relationship between management accounting information and managerial decision making in the manufacturing industry.…”
Section: Hypothesis Threesupporting
confidence: 75%
“…According to Anthony (1989) and Sharman (2003), the management accountants, using the management accounting system including the performance measurement system, support manufacturing and influence the manufacturing decisions in order to align them with the company ś general strategy. Pantamee, Abubakar and Umar (2008), in their study on the relevance of management accounting information towards decision making in Nigerian manufacturing industry stated that "good decisions are to be made by management section using management accounting information, short-term tactical decision like: Make or buy decision, elimination of unprofitable product, allocation of scarce resources between competing product or departments, acceptance or rejection of an offer etc. All these are to be made by management using managerial costing techniques as a management accounting tool.…”
Section: Review Of Empirical Studiesmentioning
confidence: 99%
“…The latest version of the expanded program logic model was developed by Pantamee and Mansor (2016). The model also suggested the elements of input, process, output and outcome to be included in a tax administration performance.…”
Section: Literature Review 20mentioning
confidence: 99%
“…The taxes over 70 per cent of the total revenue of the country's budget system are the most significant source for their formation [14]. This increases the importance of tax administration as one of the key elements for public administration of the economy, ensuring tax collection and budget tax revenues, and, as a result, the country's economic and social development [22]. The level of tax administration development is an indicator of the tax system condition, its integrity, and its stability [6].…”
Section: Target Settingmentioning
confidence: 99%